“Next Unto the Gods My Life Shall Be Spent in Contemplation of Him”: Margaret Cavendish’s Dramatised Widowhood in Bell in Campo (I&II) - Bronk, Katarzyna (Studia Anglica Posnaniensia, 2017)
Cavendish’s two-partite play Bell in Campo (1662) is a fantasy on the world where women can fight united not only against misogyny but also against an actual enemy. While the two plays seem to be focused on the valiant Lady Victoria and her female “Noble Heroicks”, Bell in Campo likewise offers an odd subplot featuring two widows and their lives without their beloved husbands. In the secular discourse of the seventeenth century, widowhood has been seen as either liberating – as when the woman became the sole owner of her husband’s estate and goods, or regained her own, and thus more independent – or degrading – when she became the not-so-welcomed burden on her children’s shoulders and pockets. Other studies on widowhood likewise state its symbolic function, showing women as the bearers of memory, predominantly of the husband and his virtues, and often attending to the spouse’s site of memory. While discussing the cultural history of properly performed widowhood, seen as the final (st)age of a woman’s life, and taking into account Cavendish’s remarkable biography, the present paper offers a close study of her propositions for appropriate widowhood and its positioning in contrast to other states of womankind as presented in Bell in Campo.1 It will likewise take into account the more or less sublimated evidence for gerontophobia, particularly in relation to women, as shown in Cavendish’s play and seventeenth-century culture.